2021
DOI: 10.3390/molecules26164917
|View full text |Cite
|
Sign up to set email alerts
|

Skin Wound Healing: Normal Macrophage Function and Macrophage Dysfunction in Diabetic Wounds

Abstract: Macrophages play a prominent role in wound healing. In the early stages, they promote inflammation and remove pathogens, wound debris, and cells that have apoptosed. Later in the repair process, they dampen inflammation and secrete factors that regulate the proliferation, differentiation, and migration of keratinocytes, fibroblasts, and endothelial cells, leading to neovascularisation and wound closure. The macrophages that coordinate this repair process are complex: they originate from different sources and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
124
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(158 citation statements)
references
References 69 publications
0
124
0
2
Order By: Relevance
“…Importantly, the overexpression of miR-145-5p increased the number of M2 macrophages (CD206 + ) in diabetic wound. It has been demonstrated that macrophages of M2 facilitate the resolution of inflammation and promote tissue remodeling by releasing growth cytokines and antiinflammatory cytokines (10,11). Therefore, the polarization of macrophage toward the M2 phenotype mediated by miR-145a-5p might be an important mechanism responsible for its therapeutic effects on diabetic wound repair.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the overexpression of miR-145-5p increased the number of M2 macrophages (CD206 + ) in diabetic wound. It has been demonstrated that macrophages of M2 facilitate the resolution of inflammation and promote tissue remodeling by releasing growth cytokines and antiinflammatory cytokines (10,11). Therefore, the polarization of macrophage toward the M2 phenotype mediated by miR-145a-5p might be an important mechanism responsible for its therapeutic effects on diabetic wound repair.…”
Section: Discussionmentioning
confidence: 99%
“…In the wound healing process, macrophages can differentiate into pro-inflammatory (M1) and anti-inflammatory (M2) phenotypes. M1 macrophages promote inflammatory response to clear the infection in the inflammatory phase of wound healing, on the contrary, M2 macrophages play a crucial role in immune regulation and tissue remodeling [ 37 , 38 ]. Strengthening the M1-to-M2 phase transition of macrophages can help block persistent inflammation and spur chronic wound healing.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the wounds of the SuDe group showed a score density of 1/3 and diffuse distribution pattern while SuDe + Lp had a score density of 2/3 and 3/3 with both diffuse and bottom distribution pattern. It is tempting to speculate that this switch in macrophage phenotype and the increased levels of M2 macrophages in the wounds of SuDe + Lp group are key for improved healing since those cells are capable of secreting anti-inflammatory cytokines that dampen inflammation and growth factors necessary for proliferation, migration, and the repair process [ 18 ]. More detailed kinetics studies of the effect of the SuDe + Lp treatment in the switch of macrophages phenotype form M1 to M2, their expression of cytokines and grow factors, as well as their patterns of distribution in the tissue could help us understand the cellular and molecular mechanisms involved in the ability of L. plantarum cultures to improve the healing time.…”
Section: Discussionmentioning
confidence: 99%